2014
DOI: 10.1073/pnas.1407395111
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of the dopamine 1-class receptors, D1R and D5R, in hippocampal dependent memory

Abstract: Activation of the hippocampal dopamine 1-class receptors (D1R and D5R) are implicated in contextual fear conditioning (CFC). However, the specific role of the D1R versus D5R in hippocampal dependent CFC has not been investigated. Generation of D1R-and D5R-specific in situ hybridization probes showed that D1R and D5R mRNA expression was greatest in the dentate gyrus (DG) of the hippocampus. To identify the role of each receptor in CFC we generated spatially restricted KO mice that lack either the D1R or D5R in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 47 publications
(54 reference statements)
9
98
0
Order By: Relevance
“…Recent compelling evidence indicates that the DG is also a key structure for CFC, perhaps the main structure involved (304,350,518,556,574). As discussed above, long-standing research has suggested repeatedly that the hippocampus is used mostly for the encoding and early storage of contextual fear and the amygdala is used essentially for modulation (265,(401)(402)(403)(404)545).…”
Section: Hippocampus Amygdala Infralimbic Ventromedial Prefrontmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent compelling evidence indicates that the DG is also a key structure for CFC, perhaps the main structure involved (304,350,518,556,574). As discussed above, long-standing research has suggested repeatedly that the hippocampus is used mostly for the encoding and early storage of contextual fear and the amygdala is used essentially for modulation (265,(401)(402)(403)(404)545).…”
Section: Hippocampus Amygdala Infralimbic Ventromedial Prefrontmentioning
confidence: 99%
“…Nowadays hippocampus and amygdala are both viewed as important for the processing of many types of information, and in particular for memory consolidation in the first few hours after acquisition (125,226,265,272,401,403,657). Fear conditioning in particular relies on CS-US interactions in the DG and in the LA (295,328,350,448,574). After all, this fits better with the findings on humans with large bilateral temporal lobe lesions (493,589), specifically those with lesions restricted to the hippocampus (308,549,664,686), who have consistently been shown to have a general incapacity to retain new declarative memories of any kind, but to remember well memories acquired weeks or months before the lesion, and, importantly, do not show appreciable deficits in scene construction (of a picture they see) while consistently losing memory items relevant to that scene (308).…”
Section: E Digression: On the Role Of Hippocampus In Learning And Mementioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not perform direct comparisons between the DH and RSC (because the experiments were performed separately, at different times, and in different behavioral rooms, resulting in different freezing levels in vehicle controls), the observed effects point toward a model of muscarinic contribution to retrieval that is multifaceted and non-uniform across brain regions. Unlike other neurotransmitter receptors such as NMDAR (Gao et al 2010), AMPA receptors (Schiapparelli et al 2006;Bannerman 2009), adrenergic receptors (Gibbs and Summers 2002;Galeotti et al 2004), and dopamine receptors (Sarinana et al 2014;Sarinana and Tonegawa 2016) for which the roles of specific receptor subunits or subtypes are clearly discriminable in various memory processes, it seems that activation of several mAChR subtypes may be necessary to maximally effect one process. This model is consistent with findings using electrophysiological approaches, which demonstrate that cortical M 1 , M 2 , and M 4 together exert a "triad of effects" (M 1 increases neuronal firing rates, M 2 mediates a decrease in cellular inhibition, and M 4 depresses excitatory transmission), which may underlie attention and learning (Gigout et al 2012).…”
Section: Discussionmentioning
confidence: 99%